Identifying lateral resistance behavior of short pile foundations in liquefaction soil - Alihudien, Arief; Munawir, As’ad; Zaika, Yulvi; Suryo, Eko Andi (Eastern-European Journal of Enterprise Technologies, 2025)
Currently, infrastructure development in earthquake-prone areas can overcome major challenges related to soil liquefaction phenomena, especially in areas with high earthquake intensity. This is a critical issue in foundation design, especially short pile foundations. One important aspect influencing the behavior of foundations in soil experiencing liquefaction is lateral resistance, which directly affects the stability and ability of the foundation to withstand lateral loads. The object of the study is to determine the lateral occupant behavior of short pile foundations with variations in vertical load, foundation depth, in liquid soil. This research was carried out with a series of tests on groups of rigid piles on sandy soil that received earthquake loads. The sand material used comes from Lumajang with a uniform density to ensure consistent soil conditions in each test. The length of the pile is determined based on the pile stiffness factor (T), with L values of 1T, 1.5T, and 2T. The vertical load applied to the pile is varied by 0.1Pu, 0.2Pu, and 0.3Pu, where Pu is the ultimate load of the pile. The research results show that pore water pressure fluctuations can be an indicator of significant liquefaction potential. Specifically, at a soil density of 20 %, the pore water pressure fluctuates in the range of 1 to 3 kPa and can reach Ru values close to or equal to 1. Another result is that the relationship between lateral deformation and lateral load in pile foundations shows an increase in linear load, and lateral deformation is not the only factor that influences the load resistance of piles. However, there are also factors such as soil conditions and the characteristics of the pile material itself